STRUCTURAL EVOLUTION OF DEMOGRAPHIC INDICATORS ON DIVORCES IN ROMANIA: A COMPARATIVE ANALYSIS BY RESIDENCE, REGIONS, AND SOCIO-DEMOGRAPHIC CHARACTERISTICS - Marius I. STUPARIU; Marcu Simion STAȘAC; Ribana LINC (Analele Universităţii din Oradea: Seria Geografie)
The present study analyzes the evolution of the divorces in Romania over the period 1992-2023, aiming to investigate the social, economic, and cultural factors that have shaped family behaviors and decisions regarding the dissolution of marriages. Using an approach based on official statistical data, the research explores significant differences between urban and rural areas, identifying divergent and convergent trends regarding divorce rates, influenced by modernization, urbanization, and economic crises. The study also examines the impact of economic migration and access to education on family behavior, highlighting how these elements have contributed to structural changes in marriages and divorces in different regions of the country. The analysis focuses on factors such as the age group of spouses, marriage duration, number of minor children, and the geographical structure of divorces, providing a deep understanding of the social dynamics and changes related to the stability of marital relationships. Another important aspect of the research is the evolution of the woman's role in marriage, influenced by increased economic independence and changes in the social perception of marriage. Additionally, regional disparities are discussed, varying depending on cultural traditions, urbanization level, and the economic development of counties, as well as common challenges faced by families in different areas of Romania. The study emphasizes the complexity of divorces, offering a comprehensive perspective on current and future trends, as well as the factors that influence marriage and divorce decisions, within a constantly changing social and economic context. The research conclusions will contribute to a deeper understanding of this dynamic phenomenon, as well as to the formulation of public policies better adapted to the contemporary realities of Romanian society.